PENGARUH KOMPETENSI PROFESIONAL GURU TERHADAP KOMPETENSI KEWIRAUSAHAAN PESERTA DIDIK PADA MATA PELAJARAN PRAKARYA DAN KEWIRAUSAHAAN DI SMKN 1 SOLOK - Pasya Mutia Reflin, - (2022)
Entrepreneurial competence of students is very important to be instilled in students to be able to achieve financial independence after completing their studies, therefore professional facilities are needed in schools in the form of classrooms, practice rooms and teaching staff. This study aims to determine the effect of the professional competence of teachers on the entrepreneurial competence of students in the subjects of crafts and entrepreneurship at the State Vocational High School 1 Solok City, in this study using a quantitative approach, the data sources used in this study were primary data and secondary data, primary data is data directly obtained from respondents from filling out google forms, while secondary data comes from literature studies in the form of journals, books and laws related to research. This study involved 64 respondents consisting of 32 students in class X and 32 in class XII majoring in marketing. The results of the study showed that the professional competence of teachers had a positive effect on the entrepreneurial competence of students at the State Vocational High School 1 Solok City. This result is known from the results of a simple linear regression test with a result of .086, while for R square .265, it can be concluded that entrepreneurial competence is not only influenced by the professional competence of teachers, but also by other teacher competencies such as pedagogic, social and personality competencies. Keywords: teacher's professional competency, student's entrepreneurship competency, entrepreneurship lesson.